Effects of dilution and prolonged storage with preservative in a polyethylene container on Bevacizumab (Avastin™) for topical delivery as a nasal spray in anti-hereditary hemorrhagic telangiectasia and related therapies - Kaja, Simon (2011)
Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant vascular dysplasia and severe, recurrent epistaxis is a common clinical phenotype associated with HHT. An intranasal treatment regime of diluted Avastin™ (Bevacizumab; recombinant humanized anti-vascular epithelial growth factor immunoglobin G1) using a pulsatile nasal irrigator has proven efficacious in clinical practice. However, concerns regarding the stability of Avastin™ following dilution and prolonged storage in standard containers used for drug delivery such as polyethylene bottles have so far prevented a more widespread clinical use. Compatibility with the preservative benzalkonium chloride was also unknown. We performed a detailed biochemical and electrochemical analysis of Avastin™ and did not detect any evidence of degeneration or aggregation following dilution and prolonged, refrigerated storage. Our data provide important insight into the stability of Avastin™ and allow the consideration of novel Avastin™ formulations, including its use in a metered-dose nasal spray for the treatment of HHT and other applications.